Defamation in Islamic law, Malaysian law, and Turkish law : a comparative study - Rahman, Intan Quraisha Binti A (My University, 2021)
Hakaret, başkalarının itibar veya saygınlığını zedeleyebilecek nitelikteki açığa vurulmuş aşağılamadır. Şerefe karşı işlenen bu suçun ciddiyeti o kadar ağırdır ki; sadece İslam hukukunda değil, dünyadaki diğer tüm hukuk sistemlerinde ceza gerektiren bir suç olarak kabul edilmektedir. Bu tez; İslam, Malezya ve Türkiye'de hakaret suçunu oluşturan temel unsurları yöneten ilkelerin benzerliklerini ve farklılıklarını incelemeyi, analiz etmeyi ve karşılaştırmayı amaçlamaktadır. Bu üç hukuk sisteminin, mukayeseli çalışmaya konu olan temel konuları şunları içermektedir: Hakaret suçuna yönelik hukuk veya yürürlükteki kanunların kaynaklarına ilişkin temel meseleler, hakaret tanımları, hakaretin kategorileri, hakaretin unsurları, hakaret suçunun işlenebileceği şekiller, hakaret suçuna yönelik var olan savunmalar, hakaret suçu cezaları ve ilgili üç hukuk sisteminde siber hakaret.

Defamation is an expressed insult that may tarnish other’s reputation or goodwill. The seriousness of this offence against honour is so severe that it is not only considered as a punishable offence in Islamic law, but also by all other legal systems in the world. This thesis aims to study, analyze, compare and contrast the similarities and the differences of the principles governing the main constituent aspects of Defamation Law in Islam, Malaysia, and Turkey. The essential topics of the laws that became the subject matters for the comparative study include the substantial issues pertaining to the sources of the law or the governing laws for the offence of defamation, the definitions of defamation, the categories of defamation, the elements of defamation, the manners in which the offence of defamation may be committed, the defences available for the offence of defamation, the penalties for the offence of defamation and cyber defamation of the three respective legal systems.
İslam Malezya ve Türk hukukunda hakaret suçu : karşılaştırmalı çalışma
Keywords: Defamation; Hakaret; Islamic law; İslam hukuku; İslam hukuku; Malaysia; Malaysian Law; Malezya hukuku; Şerefe Karşı Suçlar; Turkey; Turkish Law; Türk hukuku Offences against Honour; Türkiye